2020
DOI: 10.1002/jmv.25940
|View full text |Cite
|
Sign up to set email alerts
|

Persistent viral RNA positivity during the recovery period of a patient with SARS‐CoV‐2 infection

Abstract: As an emerging infectious disease, the clinical course and virological course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection remain to be further investigated. In this case report, we described a case of SARS-CoV-2 infection with the clinical course for more than 2 months. This patient had recovered from pneumonia after treatment. The viral RNA of throat swabs became negative and the viral-specific antibodies were produced during the recovery period. However, the viral RNA reappeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
69
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 13 publications
7
69
0
1
Order By: Relevance
“…In most reports (7 reports including 13 patients) the presence of COVID-19 in urine was detected in patients with moderate to severe disease. However, in three reports the virus has been isolated from urine of patients with mild disease (one neonate, one 7 year-old girl and a 44 year-old man) 21,23,25 .…”
Section: Resultsmentioning
confidence: 99%
“…In most reports (7 reports including 13 patients) the presence of COVID-19 in urine was detected in patients with moderate to severe disease. However, in three reports the virus has been isolated from urine of patients with mild disease (one neonate, one 7 year-old girl and a 44 year-old man) 21,23,25 .…”
Section: Resultsmentioning
confidence: 99%
“…One study showed 4 cases of healthcare professionals who tested positive after hospital discharge and discontinuation of quarantine, 8 whereas another study described a single-case patient who tested positive 70 days after the onset of COVID-19. 9 However, there is only 1 study indicating the rate of recovered patients testing positive again after the quarantine period. Mei et al 4 documented that 23 of 651 patients (3%) tested positive on a retest for SARS-CoV-2 by RT-PCR assay in a routine health check.…”
Section: Discussionmentioning
confidence: 99%
“…7 Nevertheless, data show that some patients are positive on nasopharyngeal swab after being declared recovered, and thus the appropriate timing of ending COVID-19 quarantine remains undetermined. 8,9 Overall, there is no information about signs and symptoms that can predict a new positive test in patients declared recovered from COVID-19. The fact that some patients could develop a potentially long-lasting viral presence highlights an important point of vigilance for controlling the pandemic both at the individual and collective level.…”
mentioning
confidence: 99%
“…It is interesting to note that, with lower viremia, for the present case, 0.1 ≤ α ≤0.5 copies/ml, virus shedding events occur only when IIR= 0.1. The above provides an explanation for clinical observation related to positive RT-PCR results in patients who have recovered from COVID-19 22,23,24 . Following Li and collaborators 24 , the prolonged shedding of virus from recovered patients is obviously not an isolated phenomenon, but an integral component of the interaction dynamics between SARS-CoV-2 and the immune cells.…”
Section: Resultsmentioning
confidence: 82%